EFFECTS OF TWO LEAF LITTER SPECIES ON THE COLONIZATION OF MACROINVERTEBRATES IN A TROPICAL STREAM OF INDIA - S. ANBALAGAN; T. PRATHEEP; S. DINAKARAN; M. KRISHNAN (The Bioscan, 2012)
We examined the effect of two dominant leaf litter species of Pongamia pinnata and Syzygium cuminii on the colonization of macroinvertebrate community in a tropical stream of south India. The result of the leaf fall pattern of stream revealed that leaves entering regularly in to the stream for a year, and a greater proportion of leaves occurred between January and June. Out of 4 riparian vegetation features, tree shade and abundance of S. cuminii were significant predictors of macroinvertebrate assemblage variation The rate of colonization of macroinvertebrates was higher in S. cuminii than P. pinnata. Assemblages were composed of collector- filterers (38.3%), and to a lesser extent predators (36.5%) and collector-gatherers (23.4%). Of the 12 environmental variables, water temperature, pH and stream substrates were the significant predictors of macroinvertebrates assemblage colonization.